(untitled) (Journal of Informatics and Mathematical Sciences, 2012)
The notion of intuitionistic fuzzy metric space was introduced by Park [Chaos Solitons and Fractals 22(2004), 1039–1046] and the concept of D^*-metric space by Sedghi, Shobe and Zhou [Fixed Point Theory and Applications 2007, Article ID 27906, 13 pages]. In this paper, we define intuitionistic fuzzy D^*-metric space and study precompactness and metrizability in this new setup.